The Effect of Entrepreneurship Orientation and Innovation on Sustainable Business Growth SME’s Rice Box in West Jakarta - Stephanie Clarissa; Frangky Selamat; Andriew Lim (Graduate Program of Universitas Tarumanagara, 2023)
This study aims to examine whether 1) Entrepreneurial orientation has a positive relationship to sustainable business growth. 2) Innovation has a positive relationship to sustainable business growth. The research design used is quantitatie research and uses a questionnaire for data collection. The number of samples obtained by the non-probability sampling method and purposive sampling technique were collected as many as 120 rice box SME’s owner West Jakarta which are then used in this study. Data were analysed using quantitative methods and distributing questionnaire questions with google form then in taking data using a Likert scale and using data analysis techniques Structural Equation Modelling - Partial Least Square assisted by Smart PLS version 3.0 software. The level of significance was measured through a bootstrapping procedure. The results show that indeed entrepreneurial orientation has a significant positive relationship to sustainable business growth, Innovation has a significant positive relationship to sustainable business growth.